Diffusion Kurtosis Imaging for Detection of Early Brain Changes in Parkinson's Disease - Guan, Jitian; Ma, Xilun; Geng, Yiqun; Qi, Dan; Shen, Yuanyu; Shen, Zhiwei; Chen, Yanzi; Wu, Erxi; Wu, Renhua (Frontiers in Neurology, 2019)
We aimed to evaluate microscale changes in the bilateral red nucleus and substantia nigra of patients with Parkinson’s disease (PD) using diffusion kurtosis imaging (DKI). Twenty-six patients with PD (mean age: 62.5 ± 8.7 years, Hoehn-Yahr stage: 0-4.0, Unified Parkinson’s Disease Rating Scale (UPDRS) scores: 8-43) and 15 healthy controls (mean age: 59.5 ± 9.4 years) underwent DKI of the substantia nigra and red nucleus. Imaging was performed using a General Electric (GE) Signa 3.0 Tesla MR Imaging System. Patients with PD were divided into two groups consisting of 12 patients with UPDRS scores ≥30 and 14 patients with UPDRS scores <30. All DKI data processing operations were performed with commercial workstations (GE, ADW 4.6) using Functool software to generate color-coded and parametric maps of mean kurtosis (MK), fractional anisotropy (FA), and mean diffusivity (MD). MK values in the bilateral substantia nigra were significantly lower in patients with early- and advanced-stage PD than in controls. Moreover, MK values in the left substantia nigra were significantly lower in patients with advanced-stage PD than in those with early-stage PD. Patients with advanced-stage PD also exhibited significant decreases in MK values in the bilateral red nucleus relative to controls. No significant differences in FA or MD values were observed between the PD and control groups. There were no significant correlations between MK, FA, or MD values and UPDRS scores. Our findings suggest that decreased MK values in the substantia nigra may aid in determining the severity of PD and help provide early diagnoses.